2011
DOI: 10.1002/jbmr.503
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fractures in an international cohort using risk factor algorithms without BMD

Abstract: Clinical risk factors are associated with increased probability of fracture in postmenopausal women. We sought to compare prediction models using self-reported clinical risk factors, excluding bone-mineral density (BMD), to predict incident fracture among postmenopausal women. The GLOW study enrolled women aged ≥55 years were seen at 723 primary care practices in 10 countries. The population comprised 19,586 women aged ≥60 years who were not receiving anti-osteoporosis medication and were followed annually for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 14 publications
1
38
1
Order By: Relevance
“…In practice, clinicians may face a challenge in trying to introduce a second-line drug. The factors we identified as being associated with fracture while on treatment are consistent with the highest risk of fracture in untreated populations, namely, older age and having suffered a recent fragility fracture 34 . Both these factors are compatible with an advanced stage of bone deterioration with regard to mass and structure (and perhaps other components of bone strength), which the currently available therapies are not potent enough to reverse.…”
Section: Discussionmentioning
confidence: 86%
“…In practice, clinicians may face a challenge in trying to introduce a second-line drug. The factors we identified as being associated with fracture while on treatment are consistent with the highest risk of fracture in untreated populations, namely, older age and having suffered a recent fragility fracture 34 . Both these factors are compatible with an advanced stage of bone deterioration with regard to mass and structure (and perhaps other components of bone strength), which the currently available therapies are not potent enough to reverse.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, in our study, Sambrook showed that fractures could be predicted from relatively simple algorithms that performed as well as more complex ones. [28] Since older patients, non-black patients, and those with hyperparathyroidism or concomitant estrogen use tended to remain at higher risk of fracture despite being adherent to bisphosphonate treatment, these are the patients who may need to be considered early for alternative treatments or monitored more closely to decide whether they need alternative treatments. Exactly what those criteria would be beyond BMD or new fractures are uncertain, as algorithms such as FRAX are not responsive enough to therapy to reliably detect a change in risk with therapy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies argued that previous falls should be included into FRAX, since previous falls were an independent and significant risk factor for future fractures [12,28]. Nevertheless, evidence showed that models incorporating falls as a risk factor may not be superior to FRAX alone in predicting future risk of fractures [41]. In our study, a post-hoc analysis incorporating baseline falls into the models yielded similar results for both FRAX and FI to the parsimonious models (Table 2), e.g., for the per-0.01 increment the HR was 1.03 and 1.02 and the c-index was 0.61 and 0.61 for FRAX and FI respectively.…”
Section: Modelmentioning
confidence: 97%